Assessing the validity of two-dimensional video analysis for measuring lower limb joint angles during fencing lunge - Chida, Kenta; Inami, Takayuki; Yamaguchi, Shota; Nishioka, Takuya; Yoshida, Yasumasa; Kohtake, Naohiko (Frontiers in Sports and Active Living, 2024)
The fencing lunge (lunge), characterized by minimal body rotation, offers a movement well-suited for 2D video analysis. However, to the best of our knowledge, the validity of 2D video analysis for fencing has not been verified. This study aimed to validate 2D video analysis by comparing lower limb joints (hip, knee, and ankle joints) angles during lunge using both 2D video analysis and 3D motion analysis methods. Methods: Twenty-two male fencers performed lunge trials that were simultaneously recorded using eight motion capture cameras (Qualisys Miqus M1) and two digital video cameras (Sony AX-450 and AX450a). Results: The 2D video analysis results exhibited an extremely large correlation in knee joint angles of the front and rear legs in the sagittal with those from 3D motion analysis (r = 0.93-0.99). However, while a robust correlation was found between the ankle joint angles of the front and rear legs (r = 0.82-0.84), a large bias was also observed (-5.23° to -21.31°). Conversely, for the hip joints of the rear leg, a moderate correlation (r=0.31) and a large bias (-10.89°) were identified. Conclusions: The results of this study will contribute to the development of coaching using 2D video analysis in competition settings because such analysis can be a useful alternative to 3D motion analysis when measuring the knee joint angle of the front leg and rear leg in the sagittal plane. However, for the ankle joint angle, further research on the optimal shooting position and height of the digital video camera is needed, whereas for the hip joint angle, 3D motion analysis is recommended at this time.